Criteria for conceptualizing behavioral addiction should be informed by the underlying behavioral mechanism - Tunney, Richard J.; James, Richard J.E. (Wiley, 2017)
The criteria used to determine a behavioral addiction should be based on an understanding of the underlying psychological mechanisms. This should include an analysis of whether the behavior itself has psychological features that might externally determine the individual’s behavior.